Performance Analysis of Jalan Pemuda Ngabang Section Employing PKJI 2023 Method - Alyani, Amalia; Mayuni, Siti; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2024)
Roads are land transportation infrastructure that includes all parts including complementary buildings for traffic purposes, located on the surface or underground and above water surface, except railways, lorry roads, and cable roads. Jalan Pemuda Ngabang is a district road with 1.3 kilometers long and 6-meter wide traffic lanes. The Indonesian Road Capacity Guidelines (PKJI) 2023 method was employed in this study to analyze the performance of the road section. The analysis condition is divided into under existing conditions and a five-year projection period. The result of PKJI 2023 is the Degree of Saturation (DJ). Road geometric data, traffic volume, vehicle speed, and side obstacles are collected to be the primary data. Secondary data consists of the number of vehicles, population, and map of the study location. Secondary data was obtained by field survey conducted three days from 6:00 am to 6:00 pm. Study location is analyzed into 2 segment. The results show that the degree saturation on existing condition is 0.61 for segment 1 and 0.50 for segment 2 with each level of service C. 5-year projection period analysis was carried out to evaluate the road performance for 5-year forward. Analysis generate that the degree of saturation for each segments was 1.15 and 0.94 with level of service F and E. Because the value exceeded the scope limit of 0.85, some improvements were suggested to get better performance. After road improvements, the degree saturation decreased to be 0.84 from 1.15 and 0.69 from 0.94.